Errors in Islamic Calligraphy: A Short Analytical and Critical Evaluation - Muhammad Asad Latif (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2024)
The idea of undermining the familiar is to challenge the constants and its acknowledged limitations, in contrast to deconstruction and its destructive pursuit. It is accomplished by means of the reception process and the constraints imposed by the way a word or text is formed, as well as by the overall structural and design framework and, specifically, by Arabic calligraphy. This depends on how the dual phenomena and the content's presentation are understood and interpreted by the recipient. More precisely, its expressive phenomenology reveals its actuality; four chapters of research were devoted to the study of "Errors in Islamic Calligraph: A Short Review." The methodological introduction was covered in the first chapter, while the concepts of undermining the familiar and its representations in Arabic calligraphy and embodiment of content and its application in Arabic calligraphy were covered in the second. In contrast, the third chapter described the research methods and the community's approach to thirty-two compositions, from which various conclusions were drawn from the study. The most crucial idea was explained in the fourth chapter. The theoretical framework's design relationships may be the calligraphers' example. In addition to undermining the familiar and embodiment of the content for those who are interested in and concerned with Arabic calligraphy, the current study concentrated on utilizing the constructive movements and energies of letters to enhance, modernize, and revitalize the art of Arabic calligraphy. Furthermore, the study of design treatments was recommended in order to represent the material in Arabic calligraphic forms.